MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN SOSIOLOGI KELAS X IPS 1 SMA NEGERI 8 PONTIANAK - Yusrina Yusrina; Agus Sikwan; Iwan Ramadhan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe aims of this study were to see the instrinsic and extrinsic motivation of student learning in sociology learning by teachers in class X IPS 1 SMA Negeri 8 Pontianak. The general problem in this research is How is the student's motivation for learning sociology by teachers in class X IPS 1 SMA Negeri 8 Pontianak ?. With sub-problems (1) How is the intrinsic motivation of student learning in sociology learning by teachers in class X IPS 1 SMA Negeri 8 Pontianak ?, (2) How is the extrinsic motivation of student learning in sociology learning by teachers in class X IPS 1 SMA Negeri 8 Pontianak? . The method used was a qualitative method with descriptive analysis. Data collection tools used observation guidelines, interview guidelines, and documentation tools. Data analysis techniques used data collection, data presentation, and decision making. The results of this study indicated student motivation in class X IPS 1 SMA Negeri 8 Pontianak still needs extrinsic motivation which continues to be carried out by the teacher, and it was proven that students finally start to have intrinsic motivation during sociology learning, where students have started to realize the need in learning, desire success and hope for ideals.Keyword: Learning Motivation, Sociology Learning